2014
DOI: 10.1002/uog.13369
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of fetoscopic laser ablation for twin‐to‐twin transfusion syndrome in dichorionic–triamniotic triplets compared with monochorionic–diamniotic twins

Abstract: Objective To compare outcome of dichorionictriamniotic (DCTA) triplet gestations with that of a paired cohort of monochorionic-diamniotic (MCDA) twin gestations undergoing laser therapy for treatment of twin-to-twin transfusion syndrome (TTTS). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Ten of these 18 studies were excluded (see Appendix S1), leaving a total of eight studies included in the systematic review (Figure ). These eight studies included 126 triplet pregnancies (104 DCTA and 22 MCTA) treated with fetoscopic laser surgery of placental anastomoses for TTTS . The general characteristics of the studies included are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Ten of these 18 studies were excluded (see Appendix S1), leaving a total of eight studies included in the systematic review (Figure ). These eight studies included 126 triplet pregnancies (104 DCTA and 22 MCTA) treated with fetoscopic laser surgery of placental anastomoses for TTTS . The general characteristics of the studies included are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The average gestational age at delivery among monochorionic triplets is in stark contrast to the average delivery timing (32–33 weeks gestation) reported with both uncomplicated triplet gestations, and monochorionic-diamniotic twins undergoing laser photocoagulation for severe twin–twin transfusion syndrome (TTTS), but similar to dichorionic-triamniotic pregnancies with FFTS. 1 19 20 A study comparing outcomes of laser photocoagulation in 16 dichorionic triplet gestations with 32 monochorionic twins found a similar early gestational age at delivery among dichorionic triplets, with a mean gestational age of delivery of 28.5 weeks compared with 31.9 weeks for their twin counterparts ( p = 0.02). 20 …”
Section: Discussionmentioning
confidence: 99%
“…The literature search identified 5 previous studies reporting data on MCTA pregnancies with FFTS treated by endoscopic laser surgery, and the combined data from these studies with ours are shown in table 3 and figure 2 [10][11][12][13]15] . In a total of 29 such pregnancies, the pooled survival rate of at least one baby was 80.6% (95% CI 64.9-92.4), and the overall survival for all babies was 57.5% (95% CI 36.2-77.4); there was significant heterogeneity between the studies.…”
Section: Synthesis With Results From Previous Studiesmentioning
confidence: 99%
“…In sFGR with abnormal Doppler findings in the umbilical artery of the affected fetus, there is a high risk of perinatal death and handicap for both twins; the management for affected pregnancies presenting at midgestation includes endoscopic laser coagulation of the inter-twin communicating placental vessels or cord occlusion of the FGR twin [4][5][6][7][8] . Few studies in a small number of patients have reported on endoscopic laser coagulation of communicating placental vessels for the management of FFTS in MC or dichorionic (DC) triamniotic (TA) triplet pregnancies complicated by FFTS [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%